An integrated expression phenotype mapping approach defines common variants in LEP, ALOX15 and CAPNS1 associated with induction of IL-6. - Fairfax, B; Vannberg, F; Radhakrishnan, J; Hakonarson, H; Keating, B; Hill, A; Knight, J (Oxford University Press, 2010)
Interleukin-6 (IL-6) is an important modulator of inflammation and immunity whose dysregulation is associated with a number of disease states. There is evidence of significant heritability in inter-individual variation in IL6 gene expression but the genetic variants responsible for this remain to be defined. We adopted a combined approach of mapping protein and expression quantitative trait loci in peripheral blood mononuclear cells using high-density single-nucleotide polymorphism (SNP) typing for approximately 2000 loci implicated in cardiovascular, metabolic and inflammatory syndromes to show that common SNP markers and haplotypes of LEP (encoding leptin) associate with a 1.7- to 2-fold higher level of lipopolysaccharide (LPS)-induced IL-6 expression. We subsequently demonstrate that basal leptin expression significantly correlates with LPS-induced IL-6 expression and that the same variants at LEP which associate with IL-6 expression are also major determinants of leptin expression in these cells. We find that variation involving two other genomic regions, CAPNS1 (encoding calpain small subunit 1) and ALOX15 (encoding arachidonate 15-lipoxygenase), show significant association with IL-6 expression. Although this may be a subset of all such trans-acting effects, we find that the same ALOX15 variants are associated with induced expression of tumour necrosis factor and IL-1beta consistent with a broader role in acute inflammation for ALOX15. This study provides evidence of novel genetic determinants of IL-6 production with implications for understanding susceptibility to inflammatory disease processes and insight into cross talk between metabolic and inflammatory pathways. It also provides proof of concept for use of an integrated expression phenotype mapping approach.